ROMANIZATION AND RURAL DEVELOPMENT IN THE LUSITANIA REGION - Arslantaş, Yüksel; Arıcan, Ömer Faruk (Hamza ALTIN, 2024)
Following the Second Punic War between Rome and the Carthaginians on the Iberian peninsula, which dates back to 218-201 BC, Carthage lost its supremacy in Iberia in favor of Rome. The Romans captured the coastal parts of the peninsula around 206 BC and divided the region into two provinces, Hispania Ulterior and Hispania Citerior. The Iberian peninsula witnessed internal political turmoil during Rome's late republican period. Emperor Augustus divided the province of Hispania Ulterior into Lusitania and Baetica. The restoration and renovation efforts that began during the reign of Augustus continued until the second century AD, when the empire was in its greatest heyday. This study focuses on the Roman penetration of the province of Lusitania rather than its political life. The historical geography of the Iberian peninsula has been discussed in general terms, and the pre-Roman cities and rural life of the region, starting from the Iron Age, have been mentioned in general terms. The internal structuring of the province, the adaptation of the communities to Roman life and Rome's urbanization efforts in the region are examined.

Roma’nın Kartacalılar ile Iberia yarımadası üzerinde yaptıkları ve MÖ. 218-201 yıllarına tarihlenen II. Pön Savaşı neticesinde Kartaca, Iberia’daki üstünlüğünü Roma lehine kaybetmiştir. Romalılar yaklaşık MÖ. 206 yılında yarımadanın kıyı kesimlerini ele geçirmiş ve bölgeyi ilk olarak Hispania Ulterior ve Hispania Citerior olmak üzere iki eyalete ayırmışlardır. Iberia yarımadası, Roma’nın geç cumhuriyet döneminde siyasi olarak iç çalkantılarına tanık olmuştur. İmparator Augustus, Hispania Ulterior eyaletini Lusitania ve Baetica olarak ikiye bölmüştür. Augustus döneminde başlayan restorasyon ve yenilik çalışmaları imparatorluğun en parlak dönemini yaşadığı MS. II. yüzyıla kadar devam etmiştir. Çalışmamızda Lusitania eyaletinin siyasi yaşantısından çok Roma nüfuzu altına girmesi incelenmiştir. Iberia yarımadasının tarihsel coğrafyası genel hatlarıyla ele alınmış, Demir Çağı’ndan başlayarak Roma öncesi bölge kentlerine ve kırsal yaşantılarına genel hatlarıyla değinilmiştir. Eyaletin iç yapılanması, toplulukların Roma yaşamına adaptasyonu ve Roma’nın bölge üzerindeki kentleşme çalışmaları incelenmeye çalışılmıştır.
LUSITANIA BÖLGESİ’NDE ROMANİZASYON VE KENTSEL GELİŞİM
Keywords: Roman History; Roma Tarihi